Choroid plexus papilloma of the fourth ventricle: A pediatric patient - Munoz Montoya, Juan; Maldonado Moran, Miguel; Santamaria Rodriguez, Paula; Toro Lopez, Sebastian; Perez Cataño, Carlos; Luque Suarez, Juan (Asian Journal of Neurosurgery, 2019)
Choroid plexus papilloma is a low-frequency entity in both the adult and pediatric populations. Its clinical presentation is very variable as it depends on its location and length. We must always do the differential diagnosis between papilloma and other intraventricular pathologies. This article is about a case report of a pediatric patient with a Choroid plexus papilloma located in the fourth ventricle, a location that is atypical for the pediatric population.
Keywords: Choroid plexus papilloma; fourth ventricle; pediatric